Magnetic dynamics of ferrofluids: mathematical models and experimental investigations. (1st February 2017) - Wu, Kai; Tu, Liang; Su, Diqing; Wang, Jian-Ping
Abstract: Magnetite ferrofluids with unique magnetic behaviors are attractive for biomedical applications such as magnetic fluid hyperthermia and magnetic particle imaging. A precise nanoparticle-specific characterization by theoretical models and experiments to predict dynamics of ferrofluids and optimize their behaviors for emerging biomedical applications is necessary. In this paper, combining experiments and modeling, we have uncovered interesting magnetic dynamics of nanoparticles that are dependent on magnetic field strength, polymer coating of nanoparticles, viscosity of ferrofluid, and dipolar interactions. It is concluded that either by changing the magnitude of magnetic field or the concentrations of nanoparticles, we are able to convert the dominating relaxation process of magnetic nanoparticles from Néel to Brownian, and vice versa. Polymer coatings on nanoparticles and viscosity of ferrofluids are demonstrated to have varying degrees of influence on effective relaxation times of nanoparticles with different sizes and under different field strengths. Our theoretical models are used to predict the magnetic response of ferrofluid consisting of 35 nm magnetite nanoparticles under alternating magnetic fields, and it turns out that our theoretical data fits well with the experimental data.